The Burden of Cardiovascular Diseases in the Kurdistan Province, Iran, from 2011 through 2017 - Shahram Moradi; Ghobad Moradi; Bakhtiar Piroozi (Journal of Tehran University Heart Center, 2021)
Background: Calculating the burden of diseases is essential for their monitoring. The burden of cardiovascular diseases in Kurdistan Province has not been reported. This study aimed at calculating the burden of cardiovascular diseases in the Kurdistan Province from 2011 through 2017.